Rheology study of the starch gelatinization to understand the hematite depression process - Elaine Cristina Andrade; Jean Carlo Grijó Louzada; Saeed Chehreh Chelgani; Laurindo de Salles Leal Filho (Journal of Materials Research and Technology, 2024)
Gelatinization of starch by NaOH is an essential stage for this depressant preparation to enhance its water solubility through the reverse cationic flotation. No investigation has explored the rheology of the starch gelatinization to demonstrate the hematite depression completeness. To fill the gap, this study examined the influence of a wide range of SNMRs (3:1, 5:1, 7:1, 9:1) to explore the efficiency of the gelatinization process. The main aim was to highlight how starch gel preparation can influence hematite depression in cationic reverse flotation. The steady and dynamic shear rheological measurements plus optical micrographs were assessed for the starch gel gelatinization process for different SNMR conditions. Various experiment outcomes indicated that through the starch gelatinization by SNMR>6:1, the solubilization did not occur completely (due to the presence of some pristine granules) and the gels exhibited solid-like behavior, as evidenced by K′>K″,tanδ < 1, λ≥ 94.3s, and η0 ≥ 32.0 Pa s. The incomplete release of AP macromolecules into the solution was the cause of the poor hematite depression efficiency. Pretreating starch by SNMR ≤5:1 indicated a full release of both AM and AP species to the solution since the gels showed fluid-like behavior with K′<K″,tanδ >1, λ≤ 0.7s, and η0 ≤ 2.4 Pa s. However, the excessive alkalinity promoted a reduction in the hydrodynamic size of macromolecules. These findings explain the better efficiency of SNMR = 5:1 to depress hematite compared to SNMR = 3:1. In general, starch preparation with SNMR = 6:1 marked the onset of the sol-gel transition, and the gels exhibited a balance between fluid-like behavior and solid-like behavior.